Optimasi Komposisi Pakan Untuk Penggemukan Sapi Potong Menggunakan Algoritma Genetika - Muhammad Noor Taufiq; Candra Dewi; Wayan Firdaus Mahmudy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
One of the problems that exist in Indonesia is not share of the number between the demand for beef cattle with the number of local beef cattle production. This caused by the increase in the number of people in Indonesia. It makes Indonesia have large enough dependencies to import cows from abroad to fulfill the need of Indonesian people. This study tries to implement the genetic algorithm to creating a qualified mixed ration at the reasonable cost. This study is expected to be able to increase the number of local beef cattle production to fulfill the need of Indonesian people. The representation used in this study is real code in which each chromosome initialize feed materials which used. The mutation method is the random mutation, and the selection method is elitism. The result of this study found the optimal parameter at 900 population, 800 generation and the combination of cr and mr as many as 0.9 and 0 with the highest fitness is 0,6266. The result obtained in the form of ration composition recommendation at minimal cost as daily based of the nutritional need of beef cattle